Environmental awareness in the Fatimid state within the axis of environmental awareness and means of sustainability throughout history - Dr. Fayez Khalaf Omair (Journal of College of Education, 2028)
Since environmental awareness plays an important role in the life and continuity of states, it is necessary for those following the history of the Fatimid state to know whether this awareness had an influential role in its life, renaissance and development, and to what extent it affected the establishment of its institutions, and whether it was present in preserving and caring for the environment, as we find that environmental awareness was present in the thought of the Fatimid state and was embodied in various aspects, including what relates to choosing the locations of their cities, planning and organizing them, as they took into consideration the environmental factors affecting that, in addition to that they cared about preserving the environment by paying attention to agriculture and caring for forests, orchards, gardens and animals.
Keywords: Environment, environmental awareness , Fatimid state, Mahdia , Cairo